A long-term study on the effect of magnetite supplementation in continuous anaerobic digestion of dairy effluent – Enhancement in process performance and stability. (December 2016) - Baek, Gahyun; Kim, Jaai; Lee, Changsoo
Highlights: A long-term study on the effect of magnetite in continuous biomethanation was made. Magnetite supplementation was beneficial to the continuous biomethanation of whey. Methane production and process stability were improved with magnetite addition. DIET via conductive magnetite likely contributed to the enhanced biomethanation. Methanosaeta was likely involved in DIET as well as aceticlastic methanogenesis. Abstract: Interspecies electron transfer (IET) between microbial populations with different functions is critical to stable anaerobic digestion. This study, in an attempt to facilitate IET, investigated the effect of magnetite supplementation on the biomethanation of dairy effluent in continuous mode. The magnetite-added reactor (RM) was significantly more resistant and resilient to process imbalance than the reactor run without magnetite addition (RC). RC showed unstable performance with repeated process upsets, but its performance improved to be comparable to that of RM after applying magnetite supplementation. Magnetite was particularly effective in stabilizing a build-up of propionic acid and therefore improving the process robustness and reliability. The enhanced biomethanation in terms of productivity and stability was attributed to the facilitated direct IET (DIET) between exoelectrogens and methanogens via magnetite particles. Methanosaeta was the predominant methanogen group in the experimental reactors and likely played a key role in both DIET-mediated carbon dioxide-reducing and aceticlastic methanogenesis.